Aspects of the involvement, confidence and knowledge of South African registered dietitians regarding genetics and nutritional genomics - Oosthuizen, Lizalet (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MNutr)--University of Stellenbosch, 2011.